2020
DOI: 10.48550/arxiv.2002.10265
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Periodicity in fast radio bursts due to forced precession by a fallback disk

H. Tong,
W. Wang,
H. G. Wang

Abstract: Recently, a 16-day periodicity in one fast radio burst is reported. We propose that this 16-day periodicity may due to forced precession of the neutron star by a fallback disk. When the rotation axis is misaligned with the normal direction of the disk plane, the neutron star will precess. The eccentricity of the neutron star may due to rotation or strong magnetic field etc. We found that the 16-day period may be understood using typical masses of the fallback disk. Polarization observations and information abo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…Again, although known Galactic magnetars offer no clear explanation for periodic behavior at this scale (with the possible exception of candidate magnetar 1E 1613485055 which has a measured period of 6.7 hr; De Luca et al 2006), reasonable variations in the properties of extragalactic magnetars (e.g. extremely slow rotation, precession, or presence in a binary) offer a potential explanation (Lyutikov et al 2020;Levin et al 2020;Zanazzi & Lai 2020;Beniamini et al 2020;Yang & Zou 2020;Tong et al 2020). Furthermore, several FRBs have now been localized to host galaxies with low levels of star formation (Bannister et al 2019;Ravi et al 2019), uncharacteristic of the environments of magnetars in the Milky Way as being the product of relatively typical CCSNe.…”
Section: Introductionmentioning
confidence: 98%
“…Again, although known Galactic magnetars offer no clear explanation for periodic behavior at this scale (with the possible exception of candidate magnetar 1E 1613485055 which has a measured period of 6.7 hr; De Luca et al 2006), reasonable variations in the properties of extragalactic magnetars (e.g. extremely slow rotation, precession, or presence in a binary) offer a potential explanation (Lyutikov et al 2020;Levin et al 2020;Zanazzi & Lai 2020;Beniamini et al 2020;Yang & Zou 2020;Tong et al 2020). Furthermore, several FRBs have now been localized to host galaxies with low levels of star formation (Bannister et al 2019;Ravi et al 2019), uncharacteristic of the environments of magnetars in the Milky Way as being the product of relatively typical CCSNe.…”
Section: Introductionmentioning
confidence: 98%
“…Sob'yanin (2020) suggested that the forced precession is natural and can be used to explain the period of FRBs. The fallback disk and the orbit motion may also induce the force precession (Tong et al 2020;Yang & Zou 2020). Besides, the magnetar-asteroid impact model also is proposed to explain the observed periodicity (Dai & Zhong 2020).…”
Section: Introductionmentioning
confidence: 97%
“…Several models were proposed to explain the periodic activity of FRB 180916.J0158+65. In the first type of model, the ∼ 16-day period is due to magnetar free precession (Levin et al 2020;Zanazzi & Lai 2020) or orbitinduced spin precession (Yang & Zou 2020) or fallback disk-induced precession (Tong et al 2020). The basis of these studies is the early suggestion that repeating FRBs could originate from the magnetic activity of a magnetar (Popov & Postnov 2013;Lyubarsky 2014;Katz 2016;Murase et al 2016;Kashiyama & Murase 2017;Metzger et al 2017;Kumar et al 2017;Beloborodov 2017;Metzger et al 2019).…”
Section: Introductionmentioning
confidence: 99%